DEVELOPING DESCRIPTIVE WRITING MATERIAL THROUGH FLASH FOR GRADE SEVEN IN THE ACADEMIC YEAR OF 2013/2014 (English Education Journal, 2014)
The use of the interactive media is important to support teaching and learning process. It also helps the teacher and the students in getting better achievement in writing descriptive texts. This aims of this study were to find out what medium is needed and how it gave significant progress in teaching learning process. This study presented the developing flash media for enchancing seven grade students’ writing ability. The results of the try out were found that the mean of pre-test was lower than the post test. The critical value with the degree of freedom 19 at the 5% alpha level of significant is 2.093. The observed t-value is higher that critical value (2.88 > 2.00). It means that there is a significant difference before and after using flash media in teaching writing descriptive texts.  Based on the students and the teacher’s perception which gave possitive responses on the using of Flash media and the result of calculating students’ work, it can be concluded that the Flash medium is effective and can be used in teaching learning of writing descriptive text at the seventh grade of Junior High School.